Agreement on Border Monitoring Support Mission between the Government of Sudan and the Government of South Sudan (Tufts Archival Research Center, 2015)
The agreement requests the UN to endorse the agreement on the Border Monitoring Support Mission with the following additional tasks to the UNISFA mandate: 1)Provide force protection; 2)Provide observers; 3)Provide logistic and air support; 4: Provide Accommodation for national observers.